ANALISIS IMPLEMENTASI PERATURAN PEMERINTAH REPUBLIK INDONESIA NOMOR 27 TAHUN 2014 TENTANG PENGELOLAAN BARANG MILIK NEGARA/DAERAH PADA PEMERINTAH PROVINSI LAMPUNG - Ani Heryani; Joko Rahmadiono (e-JKPP, 2019)
The problems in this research are: (1) How to implement the Republic of Indonesia Government Regulation Number 27 of 2014 concerning State/Regional Property Management, in Lampung Province, (2) What are the aspects that hinder the implementation of the Republic of Indonesia Government Regulation Number 27 of 2014 concerning Management of State / Regional Property, in Lampung Province.The research method used in this research is to use a qualitative research type with descriptive analysis method. The use of this method is to study and describe qualitatively how the implementation of the Republic of Indonesia Government Regulation Number 27 of 2014 concerning State / Regional Property Management in the Lampung Provincial Government. All data were obtained directly from informants in the field using interviews and observations. The results show that the implementation of the Republic of Indonesia Government Regulation Number 27 of 2014 concerning State / Regional Property Management in the Lampung Provincial Government, has been implemented but has not been optimal because, the implementation of its program activities and financing is still fully sourced from top-down or top-down instructions, so that the implementer is only carry out the orders of stake holders only.Aspects that hinder Government Regulation of the Republic of Indonesia Number 27 of 2014 concerning State / Regional Property Management in Lampung Province, namely (1) Operational planning, has not been implemented in accordance with the plan. (2) Inventory of facilities and infrastructure has not been able to be data properly due to lack of funds prepared so that the implementer has not been able to carry out properly, (3) Maintenance of facilities and infrastructure has not been implemented properly assigned to manage state/ regional property, so that they cannot reach all state / regional assets.